TB and poverty: the effect of rifampicin-resistant TB on household income - A. Ciobanu; V. Plesca; S. Doltu; M. Manea; L. Domente; A. Dadu (IJTLD Open)
SETTING: The Republic of Moldova, one of Europe's poorest countries, also bears one of the highest burdens of rifampicin-resistant TB (RR-TB). OBJECTIVES: To trace the patients’ journey through TB in terms of the relationship with poverty and assess its determinants. DESIGN: This cross-sectional study used secondary data from a survey assessing catastrophic costs in RR-TB-affected households. RESULTS: Data were obtained from 430 RR-TB patients. The percentage of poor TB-affected households rose from 65% prior to TB to 86% after TB treatment completion (P < 0.001). Social factors leading to poverty were identified for each stage: diagnostic period (history of incarceration: cOR 2.3, 95% CI 1.1–5.2); treatment period (being unemployed or unofficially employed: cOR 6.7, 95% CI 4.3–10.0); and post-treatment (being married or cohabiting: cOR 5.7, 95% CI 2.9–11.0). Participants who had ≥3 members in their households were more likely to be poor at all TB stages: diagnostic period (cOR 5.7, 95% CI 3.7–8.8), treatment period (cOR 3.8, 95% CI 2.5–5.6) and post-treatment (cOR 7.2, 95% CI 3.6–14.3). CONCLUSION: The study identified risk factors associated with poverty at each stage of TB. These findings outline that innovative social protection policies are required to protect TB patients against poverty.